AB0342 Rheumatoid Arthritis Related Interstitial Lung Disease. Radiological Patterns and Correlations with Clinical, Serological and Demographic Features of Disease. (10th June 2014) - Sebastiani, M.; Manfredi, A.; Tonelli, R.; Spagnolo, P.; Campomori, F.; Vacchi, C.; Cocconcelli, E.; Cerri, S.; Colaci, M.; Luppi, F.; Della Casa, G.; Sverzellati, N.; et al.
Abstract : Background: Interstitial lung disease (ILD) is a relevant extra-articular manifestation of rheumatoid arthritis (RA). Usual interstitial pneumonia (UIP) is the most frequent histo-pathological pattern of RA-ILD, followed by nonspecific interstitial pneumonia (NSIP); high-resolution computed tomography (HRCT) is crucial for the evaluation of ILD patterns without recourse to lung biopsy. Clinically, significant ILD is described in about 4% of RA patients, and recent data suggest that RA-ILD may relate to smoking and/or the presence of anti-citrullinated peptides (APCA). Objectives: To identify radiological patterns of ILD in RA patients, and their correlation with clinical, serological or therapeutic features of RA Methods: Ninety-nine patients (mean age 63.6±17.2, male/female ratio 1.6), classified as RA according to 2010 ACR/EULAR criteria, who had performed at least one chest HRCT, were retrospectively recruited. For each patient disease duration, smoking habit, use of conventional and biologic DMARDs, presence and titer of APCA, rheumatoid factor (RF), antinuclear antibodies (ANA) and anti-extractable nuclear antibodies (ENA) were recorded. All HRCT images were <2.5 mm in collimation and were reconstructed using high-resolution algorithms. Radiologic patterns were categorized as definite UIP, possible UIP or inconsistent with UIP according to the most current international guidelines. Results: RA-ILD (14 definite or possible UIP and 18 inconsistent with UIP) was detected in 32/99 RA patients. No significant associations were observed between ILD and APCA, RF, ANA, ENA, disease duration, conventional and biologic DMARDs and smoking. Comparing the three groups (definite/possible UIP, inconsistent with UIP and controls) a prevalence of male gender, RF and smoking habit were observed in patients with UIP pattern (p not significant). When UIP pattern was compared with the other 85 patients (inconsistent with UIP and controls) a significant association with male gender was observed (p=.04). Moreover, patients with UIP patterns were older (72±6.9 vs 62.3±17.9 years, p=.013), despite a same disease duration compared to patients in the other two groups. Conclusions: Our data confirmed that ILD is a frequent complication of RA, although with the limits of a retrospective study. Smoking has been described as an independent predictor of ILD, and a correlation with the presence of rheumatoid factor and APCA antibodies has also been reported. Our study showed no significant associations between clinical and serological data and the presence of ILD, with the exception of male gender and older age in UIP patients. Differently by other authors no significant association was observed with APCA, neither with commonly used drugs, in particular methotrexate and anti-TNF inhibitors. Prevalence, radiological findings, and possible risk factors of RA-ILD should be further investigated in ad hoc prospective studies on large population Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4299